Effects of Polyunsaturated Fatty Acids Supplementation on the Meat Quality of Pigs: A Meta-Analysis - Wang, Liyi; Huang, Yuqin; Wang, Yizhen; Shan, Tizhong (Frontiers in Nutrition, 2021)
Polyunsaturated fatty acids (PUFAs) supplementation has been widely discussed as a strategy for improving meat quality in pig production but the effects are inconsistent. This meta-analysis was performed to comprehensively evaluate its effects on the meat quality and growth performance of pigs. We searched the PubMed and Web of Science databases (articles published from Jan 1st, 2000, and Oct 16th, 2020) and compared PUFAs-supplemented diets with control diets. We identified 1670 studies, of which 14 (with data for 752 pigs) were included in our meta-analysis. The subgroup analysis was classified as PUFA source (conjugated linoleic acid (CLA) or linseed), concentration (high or low concentration) and initial stage (growing or finishing pigs). Our analysis found that PUFAs supplementation increased the IMF content (WMD = 0.467%, 95% CI: 0.312 to 0.621, P < 0.001), decreased the meat color L* (WMD = -0.636, 95% CI: -1.225 to -0.047, P = 0.034) and pH 24 h (WMD = -0.021,95% CI: -0.032 to -0.009, P < 0.001) but had no influence on drip loss, meat color a*, b* and, pH 45 min and growth performance. Conjugated linoleic acid supplementation improved IMF content (WMD = 0.542%, 95% CI: 0.343 to 0.741, P < 0.001) and reduced meat color b* (WMD = -0.194, 95% CI: -0.344 to -0.044, P = 0.011). Linseed supplementation increased IMF content (WMD = 0.307%, 95% CI: 0.047 to 0.566, P = 0.021), decreased meat color L* (WMD = -1.740, 95% CI: -3.267 to -0.213, P = 0.026) and pH 24h (WMD = -0.034, 95% CI: -0.049 to -0.018, P < 0.001). We discovered an increase on IMF content in both high and low concentration PUFAs supplementation (WMD = 0.461%, 95% CI: -0.344 to -0.044, P < 0.001; WMD = 0.456%, 95% CI: 0.276 to 0.635, P < 0.001). Besides, we also found the effects of PUFAs supplementation on meat color L* and pH 24h are concentration- and stage-dependent. Polyunsaturated fatty acids supplementation can improve meat quality of pigs which mainly emerge in greatly increasing IMF content.